Analisis Kemampuan Membaca Menggunakan Media Panka (Papan Kata) Bagi Siswa Tunagrahita Kelas VI SLB - Chusna, Alfina Zahrotul; Gustia, Rusmalinda; Ruby, Arcivid Chorynia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This research was conducted at SLB P Kudus from April 9 to May 8, 2025 with a qualitative case study approach. The subjects of the study were nine moderate intellectually retarded students in grade VI and their class teachers. The media used was a word board (Panka) measuring 50 x 70 cm complete with letter cards, pictures, and colorful words. Data were collected through observation, interviews, and documentation, then analyzed thematically. The results showed that the use of Panka media was effective in improving students' reading skills, including letter recognition, syllables, and reading and writing simple words. The implications of this study support the use of visual and interactive media in learning similar ABK groups. Theoretically, this research strengthens the theory of visual and kinesthetic-based learning which states that students with special needs, such as moderate intellectual disabilities, require a concrete and multisensory approach in understanding academic concepts, especially reading.